Development of UP: tasks for the new government - Kripa Shankar (2002)
Uttar Pradesh has slid rather rapidly down the development ladder in the past half a century. Today the state spends most of its revenues on servicing its huge debt and what is left is expended on supporting the establishment, leaving little for development. UP needs urgently to raise more resources and, more importantly, put the funds to use in employment-generating areas which will help in poverty alleviation. - Reproduced.
Keywords: Economic and social development - India - Uttar Pradesh; Economic and social development